Avaliação longitudinal do crescimento craniofacial de indivíduos classe II tratados e não tratados - Gonçalves, Renata de Cassia [UNESP] (2013)
This research was developed in three studies. The aim of the 1st study was to evaluate the sexual dimorphism and the growth pattern of the hand-wrist bones and the cervical vertebrae, to compare the skeletal maturation determined by hand-wrist and vertebral evaluations and to develop a quantitative indicator of the vertebral skeletal maturity in Class II Brazilian subjects (n=32 children, 17F and 15M, from 7 to 9 years old). The Eklöf & Ringertz Method and the Fishman Maturation Prediction Method were used to assess the hand-wrist maturity and the Santos-Pinto Method was used to evaluate the vertebral maturity. The findings showed the girls develop earlier than boys, but the skeletal changes are larger in boys. There was a high correlation between carpal method and quantitative indicator of the 3rd cervical vertebra skeletal maturity. It was concluded that there are sexual dimorphism between boys and girls with early maturation in girls and larger growth changes in boys. The skeletal maturity can be quantitatively determined both by the hand-wrist method as cervical vertebral methods. The 2nd and 3rd studies was to evaluate the sagittal, vertical and transverse radiographic changes of the treatment in two phases of patients with Class II division 1 malocclusion taking into account the skeletal maturity through analysis of Lateral and Posteroanterior cephalometric radiographies. The sample of two groups was composed by 64 children with Class II division 1 malocclusion in mixed dentition phase, divided into 2 groups: treated and control, each containing 32 children, 17 girls and 15 boys, mean age initial 9 years. The results of the 2nd study showed sagittal and vertical dentoskeletal changes induced by the 1st phase of two-phase treatment, such as maxillary restriction; increased mandibular length; increasing in the upper and lower anterior alveolar heights; reduction of the overjet and of the Class...